2023
DOI: 10.1099/mgen.0.001087
|View full text |Cite
|
Sign up to set email alerts
|

Economic and health impact modelling of a whole genome sequencing-led intervention strategy for bacterial healthcare-associated infections for England and for the USA

Abstract: Bacterial healthcare-associated infections (HAIs) are a substantial source of global morbidity and mortality. The estimated cost associated with HAIs ranges from $35 to $45 billion in the USA alone. The costs and accessibility of whole genome sequencing (WGS) of bacteria and the lack of sufficiently accurate, high-resolution, scalable and accessible analysis for strain identification are being addressed. Thus, it is timely to determine the economic viability and impact of routine diagnostic bacterial genomics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“… 87–90 Recent impact modelling for the UK estimated routine WGS-based surveillance could prevent 74 408 HAIs and 1257 deaths while saving £478 million, or £7.83 per £1 invested. 91 In our setting, an outbreak of VREfm was suspected 3 weeks after the study collection period when P9 and P49 developed bloodstream infection concurrently, as this represented an excess of invasive VREfm in the patient population. On the basis of our analysis, this was many weeks after VREfm transmission had probably occurred (Figures 1 and 4 ).…”
Section: Resultsmentioning
confidence: 90%
“… 87–90 Recent impact modelling for the UK estimated routine WGS-based surveillance could prevent 74 408 HAIs and 1257 deaths while saving £478 million, or £7.83 per £1 invested. 91 In our setting, an outbreak of VREfm was suspected 3 weeks after the study collection period when P9 and P49 developed bloodstream infection concurrently, as this represented an excess of invasive VREfm in the patient population. On the basis of our analysis, this was many weeks after VREfm transmission had probably occurred (Figures 1 and 4 ).…”
Section: Resultsmentioning
confidence: 90%
“…A study has been conducted to model the economic impact of a WGS surveillance system for proactive detections and interventions for nosocomial infections and outbreaks compared to the classical standard of care without WGS [ 104 ]. Inputs from national statistics and peer-reviewed articles were used to determine the economic effect of conducting a WGS-led surveillance system addressing the most common nosocomial pathogens in England and the USA.…”
Section: Wgs In Epidemiologic Tracking Of Bacterial Healthcare-associ...mentioning
confidence: 99%
“…Furthermore, it was associated with the prevention of 74,408 HAIs and 1,257 deaths. The net cost saving by using WGS was GBP 478.3 million [ 104 ]. The USA model showed that the bacterial HAI care baseline costs were about $18.3 billion.…”
Section: Wgs In Epidemiologic Tracking Of Bacterial Healthcare-associ...mentioning
confidence: 99%
See 1 more Smart Citation